PENGGAMBARAN KARAKTER TOKOH UTAMA PADA KOMIK DORAEMON KARYA FUJIKO F FUJIO - Sihombing, Anitawati; Muzakka, Moh; Fadli, Zaki Ainul (Japanese Literature, 2016)
The research is description the characteristic of the main character of Doraemon, which is Nobita. The researcher uses structural approaches to describe the structure aspect (character, characteristic and moral value of the main character) as the main base in analyzing the characteristic of the main character. The researcher uses Doraemon Comic seri 22 and 23 too. The result of the analyzing the description character of main character in Doraemon is Nobita is a main character was a protagonis and in his old he has a developing character. Characteristic of Nobita is want to help someone, intrepid, spoiled, obsessed and lazy. The result of the moral value of main character is any a positive value and negative value, the postive value of main character is to defend the truth and like to help someone, but the negative value of the main character is spoiled.